(untitled) (Al-Qamar, 2024)
Dr. Muhammad Tahir Mansoori, eminent Scholar of Islam, has written several books on different topics of Islamic Law In addition to his Research Articles. Dr Mansoori has taught and written on Fiqh and Usool-e-Fiqh matters for over two decades. He wrote a book Family Law in Islam) Theory and Applications (This book is a systematic exposition of Shari’ah rules of Muslim marriage contract on which family organization is structured. It explains legal injunctions on important issues of marital relations and family organization. This research explores and investigates the ideals and precepts on marriage and divorce both in classical jurisprudence as well as in the modern legal codes of personal status of Muslim countries. This research highlights areas of tension between the classical jurisprudence and the modern legislation on a number of issues of Islamic Family Law. The concerned book has different chapters which are related to married life i.e Dower, contract of marriage, duties and obligations of spouse, Maintenance, Dissolution of marriage, Talaq, Khula, Iddat, Raju, Custody and care of children. In this article we have discussed concepts of dissolution of marriage, Talaq, its procedure, Types, Expression of Words, its legitimacy, Dower and viewpoints of jurists about it. The purpose of this study is to introduce conjugal rights in Islamic perspective which will be beneficial to understand the sensitivity of married life. Theoretical frame work is literature review of the book of Dr. Tahir Mansoori i.e Family Law in Islam, Quranic Verses and Hadith